Social Media Influencer Attributes’ Impact on Generation Z Filipino Consumers’ Perceived Parasocial Relationships and Purchasing Behavior - Balatero, Ma Veronica (Ilomata International Journal of Management, 2026)
This study investigates the role of social media influencers (SMIs) in shaping the purchasing behavior of Filipino Generation Z consumers, with particular emphasis on how influencer attributes foster parasocial relationships (PSRs) that drive online shopping. A quantitative-descriptive research design was employed using survey data collected from 380 Generation Z respondents in San Fernando, La Union. The data were analyzed using descriptive statistics, the Mann-Whitney U test, and Spearman’s rho correlation. The results revealed that nano-influencers (with 0–10,000 followers) are the most effective in establishing trust and emotional connections with their audiences. Influencer attributes, including authenticity, content style, perceived fit, and popularity, were identified as key drivers of engagement. Gender differences were observed in the strength of PSRs, with higher levels reported among female respondents, although no significant differences were found in purchasing behavior. The study concludes that relatable and emotionally resonant influencers play a central role in influencing Generation Z’s online purchasing decisions. It recommends that brands prioritize collaborations with credible nano-influencers to enhance consumer trust and loyalty. By situating these findings within the Philippine context, the research contributes to the literature on influencer marketing and offers practical implications for post-pandemic digital strategies.